Characterization of Combustion in Cylindrical Meso-Scale Combustor with Wire Mesh Flame Holder as Initiation of Energy Source for Future Vehicles - Andi Sanata; Nasrul Ilminnafik; Muhammad Maulana Asyhar; Hendry Y. Nanlohy; Franciscus Xaverius Kristianta; Imam Sholahuddin (Universitas Muhammadiyah Magelang, 2024)
The research aims to analyze and reveal combustion characteristics in a Cylindrical Meso Scale (CMS) Combustor with a wire mesh flame holder as a reference for designing a compact, efficient, and high-density energy source for future vehicles. This experiment analyzes the combustion ’s of a butane gas (C4H10)-air mixture in a cylindrical meso-scale (CMS) combustor with the addition of wire mesh flame holder on the stability of the combustion flame, as initiation of future vehicle energy source. The diameter of the CMS combustor with wire mesh flame holder is varied to give an idea of the effect of heat loss on the combustion flame's characteristics. The results show that the wire mesh as a flame holder is essential in the combustion stabilization mechanism. A stable flame can be stabilized in a CMS combustor with wire mesh. Variations in the diameter of the CMS combustor will result in variations in the surface-to-volume ratio, heat loss, and contact area of the wire mesh flame holder. At a large diameter, it produces the characteristics of a combustion flame with a more stable flame stability limit than a smaller diameter, a dimmer flame visualization than a smaller diameter at the same air and fuel discharge, a more distributed flame mode map area than the smaller diameter, lower flame temperature and combustor wall temperature than the smaller diameter, and relatively higher energy output than the smaller diameter.